Cinderella - Davidson, Susanna; Fiorin, Fabiano (Usborne Publishing Ltd UK, 2011)
A delightful retelling of the much-loved tale. Full colour illustrations throughout. Part of Young Reading Series 1 for readers just starting to read alone.